A Molecular Nanotube with Three‐Dimensional π‐Conjugation1. (7th May 2015) - Neuhaus, Patrik; Cnossen, Arjen; Gong, Juliane Q.; Herz, Laura M.; Anderson, Harry L.
Abstract A π‐conjugated twelve‐porphyrin tube is synthesized in 32 % yield by a template‐directed coupling reaction that joins together six porphyrin dimers, forming twelve new CC bonds. The nanotube has two bound templates, enclosing an internal volume of approximately 4.5 nm3. Its UV/Vis/NIR absorption and fluorescence spectra resemble those of a previously reported six‐porphyrin ring, but are red‐shifted by approximately 300 cm−1, reflecting increased conjugation. Ultrafast fluorescence spectroscopy demonstrates extensive excited‐state delocalization. Transfer of electronic excitation from an initially formed state polarized in the direction of the nanotube axis (z axis) to an excited state polarized in the xy plane occurs within 200 fs, resulting in a negative fluorescence anisotropy on excitation at 742 nm.